Особенности пространственно-временной структуры поля скорости ветра в метеорной зоне - Кащеев, Б. Л.; Нечитайленко, В. А.; Олейников, А. Н.; Шевчук, В. А. (My University, 1988)
A study of the capability of the "observation—interpretation" system and procedure aimed at revealing pe culiar features of the spatial and the tern — poral structure of the wind velocity field in the range of altitudes from 80 to 105 km was carried out by simultaneous measurements of the wind velocity using the protractor meteor radars in two mutually perpendicular directions. A tendency towards the advance of dynamic processes in higher layers of the meteor zone was established.
Keywords: структуры поля; метеорная зона; метеор; радар